Pengaruh Service Quality, Brand Trust dan Customer Satisfaction terhadap Loyalty pada Pengguna Jasa Pembayaran Online - Oktavian, Sandy; Suhud, Usep; Febrilia, Ika (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
ABSTRACT The purpose of this study is to test whether brand reputation and transaction safety have a positive effect on brand trust. And to test service quality, brand trust, and customer satisfaction have a positive effect on customer loyalty for users of Lazada online shop pay later services. The data collection method used a survey method with the instrument in the form of a questionnaire. The object of this research is 240 respondents who have used the Lazada application service. Technical data analysis using SEM to process and analyse research data. The results of the study show that: 1) service quality has a positive effect on customer loyalty; 2) customer satisfaction has a positive effect on customer loyalty. 3) brand reputation has a positive effect on brand trust; 4) transaction safety has a positive effect on brand trust; 5) brand trust has a positive effect on customer loyalty. Keywords: Brand Reputation, Transaction Safety, Service Quality, Brand Trust, Customer Satisfaction, Customer Loyalty. ABSTRAK Tujuan dari penelitian ini adalah untuk menguji apakah brand reputation dan transaction safety berpengaruh positif terhadap brand trust. Dan untuk menguji service quality, brand trust dan customer satisfaction berpengaruh positif terhadap customer loyalty bagi pengguna jasa pay later online shop Lazada. Metode pengumpulan data menggunakan metode survey dengan instrument berupa kuesioner. Objek penelitian ini adalah 240 responden yang sudah menggunakan layanan aplikasi Lazada. Teknis analisis data menggunakan SEM untuk mengolah dan menganalisis data hasil penelitian. Hasil penelitian menunjukan bahwa : 1) service quality berpengaruh positif terhadap customer loyalty; 2) customer satisfaction berpengaruh positif terhadap customer loyalty. 3) brand reputation berpengaruh positif terhadap brand trust; 4) transaction safety berpengaruh positif terhadap brand trust; 5) brand trust berpengaruh positif terhadap customer loyalty.. Kata kunci: Brand Reputation, Transaction Safety, Service Quality, Brand Trust, Customer Satisfaction, Customer Loyalty